2021
DOI: 10.1088/1748-605x/ac2595
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability, high strength, and 3D printable alginate hydrogel for cartilage tissue engineering application

Abstract: Cartilage damage is one of the main causes of disability, and 3D bioprinting technology can produce complex structures that are particularly suitable for constructing a customized and irregular tissue engineering scaffold for cartilage repair. Alginate is an attractive biomaterial for bioinks because of its good biological safety profile and fast ionic gelation. However, ionically crosslinked alginate hydrogels are recognized as lacking enough mechanical property and long-term stability due to ion exchange. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Stem cell-laden alginate-based 3D bioprinting structures have been used in different tissues including bones, cartilage, cardiac, and blood vessels ( Choe et al, 2019 ; Chu et al, 2021 ; De Santis et al, 2021 ). However, two main disadvantages challenge the development: one is the loss of the shape fidelity and integrity after being printed due to the weak mechanical property and the other is the impairment to the adhesion and proliferation of the stem cell.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell-laden alginate-based 3D bioprinting structures have been used in different tissues including bones, cartilage, cardiac, and blood vessels ( Choe et al, 2019 ; Chu et al, 2021 ; De Santis et al, 2021 ). However, two main disadvantages challenge the development: one is the loss of the shape fidelity and integrity after being printed due to the weak mechanical property and the other is the impairment to the adhesion and proliferation of the stem cell.…”
Section: Introductionmentioning
confidence: 99%
“…With this goal, alginate was either chemically modified or engineered (sulfhydrylation, alkylation, dopamine modification) [349,354,359,361,376] or combined with other materials or compounds in order to generate mechanically stronger composite systems adapted for cartilage engineering [116,326,346,[350][351][352][353][355][356][357][358]360,[362][363][364][365][369][370][371][372]379].…”
Section: Emerging Alginate Systems With Improved Mechanical Propertie...mentioning
confidence: 99%
“…In the literature, there is evidence that ionically crosslinked ALG features low mechanical properties and long-term stability due to ion exchange. For these reasons, Chu et al [ 60 ] developed a double crosslinked ALG (DC-ALG) bioink for 3D bioprinting. The study demonstrated that human umbilical cord MSCs could differentiate into chondrocytes after 4 weeks of culture.…”
Section: Naturally-derived Bioinks For 3d Bioprinting Of Cartilage Ti...mentioning
confidence: 99%
“…In particular, the authors sequentially modified ALG with L-cysteine and 5-norbornene-2-methylamine and crosslinked scaffolds were obtained using CaCl 2 and ultraviolet (UV) light. The structures showed stronger mechanical properties, similar to native cartilage, good cell viability and chondrogenic potential, indicating cartilage tissue development [ 60 ]. DC-ALG showed a prolonged stability (4 weeks), preserving 60% of its original weight after 30 days.…”
Section: Naturally-derived Bioinks For 3d Bioprinting Of Cartilage Ti...mentioning
confidence: 99%